The Paradox of Employee Performance in Contemporary Human Resource Management Practices - Sonya Sidjabat; Muhamad Ridwan (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study purposed to analyze the dynamics of employee performance in human resource management model. A qualitative method with a case study design was used to explore the phenomenon in an organizational context. Data were collected using documentations, observations and in-depth interviews with employees and managers purposely selected for this research. The interactive model of Miles and Huberman was used for the data analysis, including data reduction, display and conclusion drawing. The results indicate the multivariate interaction effect that all HRM practices, work motivation due to individual disposition, leadership action, organizational culture and adaptation to digital transformation processes in a company create on employee performance. Results The study found an incongruity between the HRM policies and their application as well as a prevalence of extrinsic motivation over intrinsic motivation. Moreover, the adaptive brand leadership and collaborative organizational culture enhances employee performance. Digital transformation poses existential challenges and opportunities in doing performance better. This study argues that the simultaneous application of structural, behavioral and technological aspects within HRM practices is necessary to enhance employee performance